Grafik Penentuan Komposisi Campuran Agregat Material Pengaspalan Jalan Memanfaatkan Metode Digital Differential Analyzer (DDA) - Anisya, Anisya (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2018)
The more advanced technology can make it easier for someone to do their work. Included in it in terms of making graphics that can be done using computer assistance. Where computers can represent human work functions. This study aims to create an application graph for the determination of the composition of the aggregate mixture and provide the results of the calculation of the percentage of each aggregate and provide recommendations whether the composition of the aggregate mixture is feasible or not to be used. The results of this study are a graphical application for determining the value of the composition of the aggregate mixture. This application has been tested using DOSBox and TURBO C ++. Based on the results of these trials it can be concluded that the application of graphs to determine the value of aggregate mixture composition can be used as a tool for making graphs of aggregate mixtures and determining the value of aggregate composition and providing recommendations in the form of recommendations.